The problem of religious knowledge : the impact of philosophical analysis on the question of religious knowledge - Blackstone, William T. 1931- (A Spectrum book, 1963)
"This book is designed for those who have this concern and puzzlement (though, of course, it offers no guarantee of resolving such puzzlement). It is not designed to be a highly specialized and technical treatise in philosophy of religion but one which can be read and appreciated by students and educated laymen. It has two specific purposes, that of providing a clear picture of development in contemporary philosophy and the impact of these developments in philosophy of religion, and that of systematically exploring the question, "Is there religious knowledge?" Contemporary philosophy is used as a point of reference for devising a framework within which this question can be answered. Space limitations have forced an all-to-brief treatment of some positions. Such brevity tends to distort but I have made efforts to avoid such distortion."--Author's Preface.